2003
DOI: 10.1046/j.1471-4159.2003.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium enhances long‐term potentiation independently of hippocampal neurogenesis in the rat dentate gyrus

Abstract: We measured the temporal and spatial profiles of neural precursor cells, hippocampal long-term potentiation (LTP), and signaling molecules in neurogenesis-induced adult rats. Chronic lithium treatment produced a significant 54% and 40% increase in the numbers of bromodeoxyuridine [BrdU(+)] cells after 12 h and 28 days, respectively, after treatment completion in the dentate gyrus (DG). Both LTP obtained from slices perfused with artificial cerebrospinal fluid (ACSF-LTP) and LTP recorded in the presence of bicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 33 publications
5
68
2
2
Order By: Relevance
“…It has been reported that lithium stimulates progenitor proliferation in cultured brain neurons (Hashimoto et al, 2003), shifts the phenotype from predominantly astrocytic to neuronal (Kim et al, 2004), and inhibits apoptosis of mouse NSPCs (Shimomura et al, 2003). In vivo, lithium enhances proliferation of DG progenitor cells (Chen et al, 2000;Son et al, 2003). In this study, we found that lithium increased hippocampal proliferation also in the immature brain and that the effect was long-lasting (at least 7 weeks) as indicated by PhH3 labeling, both in controls and after HI.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It has been reported that lithium stimulates progenitor proliferation in cultured brain neurons (Hashimoto et al, 2003), shifts the phenotype from predominantly astrocytic to neuronal (Kim et al, 2004), and inhibits apoptosis of mouse NSPCs (Shimomura et al, 2003). In vivo, lithium enhances proliferation of DG progenitor cells (Chen et al, 2000;Son et al, 2003). In this study, we found that lithium increased hippocampal proliferation also in the immature brain and that the effect was long-lasting (at least 7 weeks) as indicated by PhH3 labeling, both in controls and after HI.…”
Section: Discussionsupporting
confidence: 57%
“…GSK-3b has multiple roles and inhibiting GSK-3b enhances hippocampal progenitor proliferation (Wexler et al, 2008). Previous studies reported that lithium could increase neural stem/progenitor cell (NSPC) proliferation without affecting differentiation (Son et al, 2003), whereas others found that lithium primarily promoted neuronal differentiation (Chen et al, 2000;Kim et al, 2004) in the adult rodent brain. In the immature brain, however, the basal NSPC proliferation rate is higher and relative differentiation levels are different (Qiu et al, 2007;Zhu et al, 2009c).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also found that only acute treatment resulted in a decrease in CREB phosphorylation (Rantamaki et al, 2006) or that chronic lithium treatment caused an increase in CREB phosphorylation (Einat et al, 2003;Kim et al, 2004). Son et al (2003) found an increase in CREB phosphorylation in rat cerebellar granule cells only after acute treatment for 2 days. As we did not find any changes in gene expression after acute treatment, we did not determine CREB phosphorylation after 24 h. The reason for these diverging results is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, recent reports have described that Li and VPA affect neurogenesis through increasing cell proliferation and/or promotion of neuronal differentiation of neural precursor cells (Chen et al, 2000;Son et al, 2003;Hao et al, 2004;Hsieh et al, 2004;Kim JS et al, 2004;Laeng et al, 2004;Wexler et al, 2008) and that Li blocks the effects of stress on depression-like behaviors through increasing hippocampal neurogenesis in adult rodent models (Silva et al, 2008). Results of these studies suggest that adult hippocampal neurogenesis plays an important role in the therapeutic action of mood stabilizers as well.…”
Section: Introductionmentioning
confidence: 94%